مدى الاستفادة من زخارف المصوغات التقليدية لتنمية الإبداع الفني وترسيخ الثقافة التراثية الفنية لدى طلبة المرحلة الثانوية بدولة الكويث - السالم، نورية حمد (جامعة اليرموك - عمادة البحث العلمي, 2021)
هدفت الدراسة إلى التعرف إلى مدى الاستفادة من زخارف المصوغات التقليدية في التراث الكويتي في تنمية الإبداع الفني وترسيخ الثقافة التراثية الفنية لدى طلبة المرحلة الثانوية؛ وذلك من وجهة نظر معلمي التربية الفنية. وعليه فقد قامت الباحثة بإعداد أداة خاصة بالدراسة تكونت من (45) عبارة تناولت خمسة محاور؛ هي إدارة المدرسة، والمناهج والأنشطة، والمعلم، والبيئة المدرسية، وترسيخ الثقافة التراثية الفنية، تم تطبيقها على عينة تكونت من 120 من معلمي التربية الفنية في المرحلة الثانوية بدولة الكويت. وتوصلت نتائج الدراسة إلى أن هناك تقديرات من وجهة نظر هؤلاء المعلمين في إمكانية الاستفادة من زخارف المصوغات التقليدية في تنمية الإبداع الفني لدى الطلبة وذلك بدرجة متوسطة. وأفادت العينة بأن توظيف هذه الزخارف ينعكس على ترسيخ الثقافة التراثية الفنية لدى الطلبة بدرجة كبيرة. كما تبين عدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات أفراد العينة حول تقديراتهم لدور المنظومة التعليمية المدرسية في الإفادة من زخارف المصوغات التقليدية في تنمية الإبداع الفني لدى الطلبة، وكذلك حول انعكاسات ذلك على ترسيخ الثقافة التراثية الفنية تبعا لمتغيرات النوع، وعدد سنوات الخبرة. The study aimed to identify the role of the elements of the school education system in utilizing the traditional Kuwaiti jewelry decoration heritage in the development of artistic creativity among high school students in Kuwait and monitor the most important results of investing in the use of these decorations in the consolidation of cultural heritage of art from the point of view of the teachers of art education. For this purpose, the researcher prepared a study tool consisting of (45) words distributed on five axes: school administration, curriculum and activities, teacher, school environment, and the consolidation of artistic heritage culture applied to a sample of (120) in the secondary stage in the State of Kuwait. The results revealed that the educational system of the school contribute to a medium degree in the use of decorations traditional jewelry to develop artistic creativity among Students. The results also revealed that the use of these decorations is reflected in the consolidation of cultural heritage of art to the students to a large extent. There were no statistically significant differences between the average scores of the sample members concerning their assessment of the role of the school system in benefiting from the traditional jewelry in the development of artistic creativity among the students, as well as the implications of this on the establishment of cultural heritage according to variables (Gender, years of experience).
Keywords: التراث الكويتي -- الثقافة التراثية -- الإبداعات الفنية -- زخارف المصوغات